CREATION OF ELECTRONIC MEDICAL BASE WITH THE HELP OF SOFTWARE PACKAGES FOR MEDICAL SERVICES IN THE REGIONS (Conferencea, 2022)
This article presents opinions on the creation of an electronic medical database of medical services in the regions using software packages, their possibilities and effective ways of using information technologies in their organization. In addition, the database and algorithm are presented in the article.